Effects of 28 days of resistance exercise while consuming commercially available pre- and post-workout supplements, NO-Shotgun(® )and NO-Synthesize(® )on body composition, muscle strength and mass, markers of protein synthesis, and clinical safety markers in males - Spillane, Mike (BioMed Central, 2011)
PURPOSE: The effects of 28 days of heavy resistance training while ingesting the pre- and post-workout supplements, NO-Shotgun(® )and NO-Synthesize(® )were determined on body composition, muscle strength and mass, markers of protein synthesis, and clinical safety markers. METHODS: Nineteen non-resistance-trained males participated in a resistance training program 4 times/week for 28 days while either ingesting 27 g/day of carbohydrate (CARB) or NO-Shotgun(® )30 min pre-exercise and 27 g/day of carbohydrate or NO- Synthesize(® )30 min post-exercise (NOSS). Data were analyzed with separate 2 × 2 ANOVA (p < 0.05). RESULTS: Total body mass was increased in both groups (p = 0.001), but not different between groups. Fat mass was unchanged with CARB, but NOSS decreased fat mass (p = 0.026). Both groups increased fat-free mass (p = 0.001); however, the increases were greater with NOSS (p = 0.023). NOSS underwent greater increases in upper-body (p = 0.023) and lower-body (p = 0.035) strength than CARB. Myofibrillar protein significantly increased in both groups (p = 0.041), with NOSS being greater than CARB (p = 0.049). All of the MHC isoforms were significantly increased in both groups; however, NOSS was greater than CARB for MHC 1 (p = 0.013) and MHC 2A (p = 0.046). All of the myogenic regulatory factors were significantly increased in both groups; however, NOSS was greater than CARB for Myo-D (p = 0.038) and MRF-4 (p = 0.001). For the whole blood and serum clinical chemistry markers, all variables remained within normal clinical ranges. CONCLUSIONS: Heavy resistance training for 28 days, with NO-Shotgun(® )and NO-Synthesize(® )ingested before and after exercise, respectively, significantly improved body composition and increased muscle mass and performance without abnormally impacting any of the clinical chemistry markers.